Finally a smoking gun - Daniel Wissmann (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2020)
Did policy interventions contribute to the gradual segmentation of lending markets starting with the 2007 - 2008 global financial crisis? We investigate this question in an international Cournot duopoly model under an equity constraint. Two symmetric multinational banks compete for corporate lending via local affiliates in two separate national lending markets. Their credit risk in each market is determined by their choice of monitoring effort, which is more costly for foreign lending. Under a binding equity constraint, our model predicts shocks to bank equity, regulatory standards and monetary policy, such as occurred during and after the crisis, to increase the home bias of multinational lending. We interpret this lending retrenchment as a flight to informationally closer or better understood lending. Our results under a non-binding equity constraint are largely identical.
urn:nbn:de:bvb:19-epub-73026-5
Keywords: I18; I12; J28; J31; K23; 330; Occupational Wage Differential; Working Conditions; Smoking; Regulated Industries